beta-Adrenergic agonist activity of a monoclonal anti-idiotypic antibody. - Guillet, J G (1985)
Hybridoma cells bearing monoclonal antibody against the beta-adrenergic ligand alprenolol were used as an immunogen to raise monoclonal anti-idiotypic antibodies. Of six anti-idiotypic antibodies, which inhibit ligand binding, three were able to recognize beta-adrenergic receptors. One of them, mAb2B4, an IgM that could be amplified into ascites, binds to the beta-adrenergic catecholamine receptors of intact epidermoid A431 cells and precipitates receptors solubilized from plasma membranes by digitonin. This antibody identifies the beta 2-adrenergic receptor of A431 cells as a single 55-kDa protein and stimulates adenylate cyclase activity. This stimulation is inhibited by the beta-adrenergic antagonist propranolol.